Pure endoscopic management of fourth ventricle arachnoid cyst: Case report and literature review - Aljohani, Hani; Romano, A; Iaccarino, C; Ganau, M; Diemidio, P; Chibbaro, S (Asian Journal of Neurosurgery, 2018)
Arachnoid cysts (ACs) within the fourth ventricle are rare, and only a few cases have been reported in the literature. These are benign lesions within the arachnoid membrane, and they have been reported to occur in almost all locations where arachnoid is present. Different procedures have been performed to restore a normal cerebrospinal fluid dynamic and/or pressure, including shunting and partial or complete excision of the cyst by open microsurgery or endoscopic fenestration. We report the case of a fourth ventricle AC successfully treated using only endoscopic anterior trans-frontal cyst fenestration/marsupialization and standard third ventriculostomy. Clinical and technical features are discussed, along with the pertinent literature.
Keywords: Arachnoid cyst; endoscopy; fenestration; fourth ventricle; marsupialization